Spinal cord grey matter pathology in multiple sclerosis - Gilmore, Christopher Patrick (2008)
Background: Traditionally, Multiple Sclerosis (MS) has been considered to be a predominantly white matter (WM) disease. More recent studies have revealed considerable grey matter (GM) involvement in the brain. However there is a paucity of literature examining GM pathology in the spinal cord.